Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas X.2 Di SMAN 1 Palembang Melalui Penerapan Metode Pembelajaran Team Games Tournament (TGT) - Septiani, Weny; Nelsi, Nelsi; Amelia, Amelia; Rosnauli, Firly; Oktarina, Santi; Nisak, Hairun; Hanan, Sholihatun Wafiyyah (SJEE (Scientific Journals of Economic Education), 2025)
The purpose of this study was to analyze the effect of Team Games Tournament (TGT) learning on student learning outcomes on anecdote text material. The method used is Classroom Action Research (PTK) with a quantitative approach, which is designed using a quasi-experimental type with a one-group pre-test-post-test design. The instruments used consisted of written tests and questionnaires. Data were collected through pre-test, post-test, and questionnaire, and analyzed using t-test. The results showed a significant difference between the learning outcomes of students before and after the application of this model. This can be seen from the average score obtained by students, where the average pretest score is lower than the post-test (67 < 79). Hypothesis testing using the t-test shows that t count > t table (14.25 > 2.03), so the alternative hypothesis (Ha) is accepted. This indicates that the application of the TGT model in Indonesian language lessons on anecdotal text material is effective in improving the learning outcomes of students in class X.2 SMA Negeri 1 Palembang. The results of the questionnaire also showed that the TGT learning model received a very positive response. Thus, it can be concluded that students find the TGT learning model as an interesting and effective process in increasing their learning motivation in Indonesian language lessons, especially on anecdote text material